Sekolah sebagai Sistem Sosial: Imperatif Fungsional dan Kesenjangan Pendidikan di Wilayah Pedesaan Indonesia - Kurniawati, Atik; Kabelen, Marista Christina Shally; Jahja, Rusfadia Saktiyanti; Afdhal, Afdhal (KOMUNITAS: Jurnal Ilmu Sosiologi, 2025)
Educational inequality in rural Indonesia reflects complex and layered structural issues. This study aims to analyze the social system functions of rural schools through Parsons’ AGIL framework (Adaptation, Goal attainment, Integration, Latency), examining how schools sustain and reproduce social structures. A qualitative case study was conducted at SMAN 13 in Tangerang Regency, representing rural schools near urban areas. Data were collected through in-depth interviews with 37 participants, participant observation, and document analysis between April and July 2025, followed by thematic analysis. The findings reveal the school’s adaptive role in responding to economic and resource limitations; goal attainment through transmitting mobility values, constrained by inadequate facilities and policies; integration through informal collaboration among schools, families, and communities; and cultural pattern maintenance via local and religious values that sometimes conflict with modernization. The study’s novelty lies in its empirical application of AGIL theory to rural schooling, offering theoretical contributions to educational sociology and providing a contextual basis for holistic policy development.